More on the Terwilliger algebra of Johnson schemes - Lv, Benjian (2014)
In Levstein and Maldonado (2007), the Terwilliger algebra of the Johnson scheme J(n,d) was determined when n≥3d. In this paper, we determine the Terwilliger algebra T for the remaining case 2d≤n<3d.